Analysis of heavy metal content and microbiological quality of fish and giant prawns chatch in Percut Watershed, Percut Sei Tuan District, Province of North Sumatra - Zulaika Haddis Nasution; Elisa Julianti; Dwi Suryanto (Depik, 2022)
The purpose of this research was to determine the content of heavy metals and microbiological quality, and compare to the requirements of the quality standard values according to SNI 2729:2013 and SNI 2705:2014, as well as to determine the value of the Bioaccumulation Factor (BAF) and the maximum consumption limit of fish and giant prawns heavy metal-concentrated. This researh used survey and random sampling methods, i.e taking research samples (tilapia, broom fish, and giant prawns) at 3 (three) observation stations, including Station 1 Amplas, Station 2 Denai, and Station 3 Percut. Heavy metal content (Pb and Cd) and microbiological quality (E.coli and Salmonella, sp) were analysed. Data analysis was done by inference and calculated using Microsoft office Excel (Microsoft Inc., USA) descriptively. The results showed that all samples in each observation did not meet the quality standard value requirements according to SNI 2729:2013 and SNI 2705:2014. The average heavy metal content of Lead (Pb) was 0,3 mg/kg in tilapia and broom fish, and 0,5 mg/kg in giant prawns. The content of heavy metal Cadmium (Cd), were 0,1 mg/kg in tilapia and broom fish, and 0,5 mg/kg in giant prawns. All samples also showed positive in containing E.coli and Salmonella, sp. The value of Bioaccumulation Factor (BAF) of heavy metals (Pb and Cd) in all samples was 1, meaning that the sample's ability to accumulate heavy metals (Pb and Cd) was high. The maximum limit for consumption of concentrated samples of heavy metals in tilapia was 0,196 kg/week, broom fish was 0,221 kg/week, and giant prawns was 0,203 kg/week.